The diagnostic value of CT-guided percutaneous lung biopsy in atypical pulmonary hamartoma and pulmonary sclerosing pneumocytoma - Li, Meng; Li, Yang; Zhao, Xiaopeng; Wang, Xiangming; Shi, Gaofeng; Zhang, Andu; Deng, Huiyan; Ren, Jialiang (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the clinical utility of computed tomography-guided percutaneous lung biopsy (CT-PLB) in the diagnosis of atypical pulmonary hamartoma (APH) and pulmonary sclerosing pneumocytoma (PSP).MethodsThis retrospective study analyzed 19 patients with pulmonary nodules who underwent CT-PLB at our hospital between October 2016 and August 2019. All patients underwent surgical excision within two weeks following CT-PLB, and the postoperative histopathological results were used as the reference standard for diagnosis. Among these patients, ten cases were confirmed as PSP and assigned to the PSP group, while nine cases were diagnosed as pulmonary hamartoma and assigned to the APH group. The diagnostic accuracy of CT-PLB for APH and PSP, as well as the incidence of procedure-related complications, were analyzed and compared.ResultsAmong the 19 patients, the overall diagnostic accuracy of CT-PLB was 89.5% (17/19). The diagnostic accuracy was 88.9% (8/9) in the APH group and 90.0% (9/10) in the PSP group. Complications included one case of minimal pneumothorax in the PSP group and one case of mild hemoptysis in the APH group. Additionally, 14 patients experienced mild to moderate pulmonary hemorrhage, including 8 cases (5 mild, 3 moderate) in the APH group and 6 cases (all mild) in the PSP group. No severe complications, such as pleural reactions, occurred in any patient.ConclusionCT-PLB demonstrates high clinical diagnostic value for both APH and PSP. The procedure is safe, reliable, and associated with few complications. Thus, it can serve as a valuable tool for preoperative clinical diagnosis.